Identification and Quantification of Polymethoxylated Flavonoids in Different Citrus Species Using UPLC-QTOF-MS/MS and HPLC-DAD - Brits, Maxime; Naessens, Tania; Theunis, Mart; Taktak, Olfa; Allouche, Noureddine; Pieters, Luc; Foubert, Kenn (Planta Medica, 2021)
Many species from the genus Citrus are used in traditional medicine and contain polymethoxylated flavonoids. These compounds show anti-inflammatory and chemopreventive activities, among others, and therefore have a big potential to be developed as therapeutic agents or dietary supplements. Citrus species are different in their profile and yield of polymethoxylated flavonoids. Therefore, polymethoxylated flavonoids were identified and quantified in seven different Citrus species, including wild-type and commercially available species. All species were profiled using UPLC-QTOF-MS/MS analysis combined with mass spectral molecular networking. A total of 38 polymethoxylated flavonoids were detected and 8 of them were present in every species. As the yield of polymethoxylated flavonoids was different for each species, a generally applicable HPLC-diode array detection method was developed and validated according to the ICH guidelines to quantify the amount of nobiletin and the total amount of polymethoxylated flavonoids expressed as nobiletin. Analysis of the seven samples showed evidence that wild-type Citrus species (e.g., Citrus depressa) contain higher yields of polymethoxylated flavonoids compared to commercially available species (e.g., Citrus limon). Qualitative analysis revealed the broadest variety of different PMFs in C. depressa, Citrus reticulata, and Citrus reticulata × Citrus sinensis, which makes them interesting sources of polymethoxylated flavonoids for future development as therapeutic agents or dietary supplements.
Keywords: Citrus; Rutaceae; PMFs; identification; molecular networking; quantification